(untitled) (Modern education and development, 2025)
Religious worldview means that the development of reality is attributed to divine power, i.e. God. Religious worldview differs in its vitality. In the religious worldview, the activities of God and man are more prominent. But all existence, movement and events in existence are covered by the religious worldview.